Sustainable enhancement of wool fibers using Hymenocrater platystegius flower and natural dyes for improved Insect-Repellent and color properties - Faezeh khazaei; Hossein Barani (Results in Chemistry, 2024)
This study investigates the application of Hymenocrater platystegius flower as a natural mothproofing agent for wool fibers and examines the effects of aluminum mordanting on the dyeing properties of wool treated with various natural dyes. Wool fibers were treated with Hymenocrater platystegius flower powder and aluminum salts, followed by dyeing with Madder, Reseda lutea, Indigo, or Walnut shell dyes using different mordanting methods. FTIR analysis revealed the characteristic absorption bands and confirmed the interactions between the wool fibers and the treatment agents. The insect-repellent properties were assessed by weight loss measurements after exposure to Anthrenus verbasci larvae, showing significant improvements in treated samples, particularly with the combination of Hymenocrater platystegius and aluminum mordanting. GC–MS analysis of the essential oil identified as α-Pinene, Trans-Verbenol, Linalool, and β-Bourbonene as the main constituents, contributing to the insect-repellent effect. The L*a*b* color space analysis demonstrated that aluminum mordanting significantly enhances the color strength and stability of dyed wool, with pre-mordanting generally providing better results. The study further evaluated the washing and light fastness, as well as the mothproofing properties of the dyed wool samples. These results indicate that the weight loss percentages of treated wool fiber after washing are slightly higher than before washing, but the difference is not significant. Overall, the use of aluminum mordant in conjunction with Hymenocrater platystegius flower powder not only improves the color characteristics of wool dyed with natural dyes but also provides effective mothproofing properties, making it a viable and eco-friendly option for textile applications.